PENGARUH KOMPRES DINGIN TERHADAP PENURUNAN NYERI PERSALINAN KALA I PADA IBU BERSALIN DI WILAYAH KERJA PUSKESMAS BATU AJI KOTA BATAM TAHUN 2018 - Nopliza, Tita; Susanti, Susanti (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2019)
Maternal labor is an effort carried out by the uterus when a baby is born. During labor, the uterus contracts and pushes the baby down to the cervix. The weight of the baby's head when moving down the birth canal also causes pressure. These things cause pain in the mother. The purpose of this study was to determine whether there was an effect of cold compress technique to relieve first stage of womenâ€™s labor pain at PuskesmasBatuAji in Batam, 2018. This study applied the design of one group pre test and post test. The population was all first stage labor, with a total sample of 30 respondents, using consecutive sampling technique. The study was conducted on May 1 to July 20 in PuskesmasBatuaji work area, Batam. The data was analyzed using T-test analysis technique. The results of the mean pain intensity before being given therapeutic communication were 6.80 + 2.57 and after that 3.30 + 3.00 of the total score 30 experienced a decrease in pain intensity by 3.5, the results of the T-test p-value 0.000 <significance limit (Î±) 0.05. In conclusion, there is a cold compress technique for relieving the first stage of maternal labor pain at PuskesmasBatuAji, Batam in 2018. It is suggested the health workers can provide cold compress techniques optimally, so that the incidence of labor pain can be minimized.Â